Phytochemical and biological studies of Panicum antidotale aerial parts ethanol extract supported by molecular docking study - Sarwar, Imtisal; Asif, Muhammad; Jamshaid, Talha; Saadullah, Malik; Zubair, Hafiz Muhammad; Saleem, Mohammad; Jamshaid, Usama; Youssef, Fadia S.; Ashour, Mohamed L.; Elhady, Sameh S. (Frontiers in Pharmacology, 2024)
Panicum antidotale has traditionally been used as a poultice to alleviate local inflammation and painful diseases. This study aimed to evaluate the anti-inflammatory, wound-healing, analgesic, and antipyretic potential of its ethanol extract (PAAPEE) in vivo for the first time. In vitro antioxidant assays of P. antidotale picrylhydrazyl-1-diphenyl-using a 2,2 assay revealed that it showed IC50 of 62.50 ± 6.85 µg/mL in contrast to standard, ascorbic acid, that showed IC50 of 85.51 ± 0.38 µg/mL. Administration of PAAPEE at a dose of 500 mg/kg (PAAPEE-500) displayed inhibition percentage in carrageenan-induced and histamine-induced edema by 78.44% and 75.13%, respectively, 6 h posttreatment compared to that of the untreated group. Furthermore, it showed 68.78% inhibition of Freund's complete adjuvant-induced edema 21 days after treatment. It reduced the animal’s rectal temperature in the yeast-induced fever model to 99.45 during the 4th h post-treatment. It significantly inhibited abnormal writhing by 44% in the acetic acid-induced pain model. PAE-500 also showed enhancement in wound closure by 72.52% with respect to that of the untreated group on the 10th day post-treatment using the excision healing of wound model. Histopathological examination of skin samples confirmed this improvement, showing enhanced tissue architecture with minimal infiltration of inflammatory cells. High-performance liquid chromatography (HPLC) of PAAPEE revealed the presence of quercetin, gallic, p-coumaric, benzoic, chlorogenic, syringic, ferulic, cinnamic, and sinapic acids. Molecular docking of 5-lipoxygenase and glycogen synthase kinase-3 β protein indicated their potential interaction within the active sites of both enzymes. Thus, P. antidotale serves as an effective natural wound-healing, anti-inflammatory, analgesic, and antipyretic agent.